2017
DOI: 10.5539/ijel.v7n6p73
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Intelligences-Based Homework and EFL Students’ Vocabulary Learning

Abstract: This paper investigates the effects of Multiple Intelligences-based homework on EFL students' vocabulary learning at a university in Vietnam. Based on the Multiple Intelligences (MI) Theory framework and Action Research approach, the homework instructions were adapted according to different types of intelligences. After four weeks of practice, it was found that students made use of different strategies to learn new words. They also showed creativity and a greater enthusiasm toward vocabulary learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Intrapersonal intelligence may be defined as the capacity to notice one's own similarities and distinctions, as well as those of others [1], [2], [9]. Then, Naturalist intelligence is the ability to recognize and classify the diverse species [2], [9], [17]. Some studies revealed that Multiple Intelligence integration gives great impacts in English teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrapersonal intelligence may be defined as the capacity to notice one's own similarities and distinctions, as well as those of others [1], [2], [9]. Then, Naturalist intelligence is the ability to recognize and classify the diverse species [2], [9], [17]. Some studies revealed that Multiple Intelligence integration gives great impacts in English teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies revealed that Multiple Intelligence integration gives great impacts in English teaching and learning. Integrating MI theory to English classroom activities can enrich vocabulary [17] and improve students' motivation [10], [15], [18]. Students' attitudes about vocabulary study shifted, and the classroom environment became more engaging [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation